Interactive Learning Media Based on Google Slides for Fifth-Grade Indonesian Language Classes: Media Pembelajaran Interaktif Berbasis Google Slides pada Pembelajaran Bahasa Indonesia Kelas V - Fausiah; Akhir, Muhammad; Paida, Andi (Indonesian Journal of Innovation Studies, 2025)
Background: Digital technology has become a crucial element of modern education, requiring innovative learning approaches that align with students’ needs. Specific Background: In elementary schools, learning activities often rely heavily on textbooks, which limit student engagement and interactivity. Knowledge Gap: Few studies have explored the use of Google Slides as a fully interactive medium combining multimedia elements for Indonesian language instruction. Aim: This study developed an interactive learning medium based on Google Slides for fifth-grade Indonesian language classes, tested its validity, practicality, and learning outcomes. Results: Media validation results were very high (82.50% and 93.75% from media experts, 82.14% and 94.64% from material experts), teacher responses reached 97.50%, and student responses 96.15%, indicating excellent practicality. Learning achievement increased from 31% (pretest) to 94% (posttest). Novelty: The media integrates internal navigation, quizzes, audio, visual, and animation into a single platform, allowing students to interact with materials actively and independently. Implications: This research offers an adaptive and replicable learning resource that supports student-centered pedagogy and can serve as a model for technology integration in primary schools. Highlight Interactive media improved student engagement and completion rates Validated and practical according to experts, teachers, and students Provides replicable model for digital-based primary education Keywords: Interactive Learning Media, Google Slides, Elementary Education, Digital Literacy, Indonesian Language Learning